A novel functionalized pillar[5]arene for forming a fluorescent switch and a molecular keypad. Issue 70 (12th July 2016) - Wei, Tai-Bao; Chen, Jin-Fa; Cheng, Xiao-Bin; Li, Hui; Lin, Qi; Yao, Hong; Zhang, You-Ming
Abstract : The sensing mechanism of the sensorPC5 to Fe 3+ . Abstract : We have synthesized a novel functionalized pillar[5]arene (PC5 ) and used it for fluorescent detection of iron ions (Fe 3+ ). It displays a specificity response for iron ions over other common cations (Hg 2+, Co 2+, Ca 2+, Ni 2+, Pb 2+, Cd 2+, Zn 2+, Cr 3+, Cu 2+, Mg 2+ and Ag + ) in a solution of DMSO/THF (1 : 4, v/v). Competitive cations did not show any significant changes in emission intensity and the fluorescence spectra detection limit was 1.25 × 10 −8 M, indicating the high selectivity and sensitivity of the sensor to Fe 3+ . It is well known that H2 PO4 − has a binding ability with Fe 3+ to form the complex (Fe(H2 PO4 )3 ), so we designed a fluorescent switch and a molecular keypad ofPC5 between Fe 3+ and H2 PO4 − . Furthermore, a thin film based on thePC5 was prepared, which was confirmed to be a convenient test kit for detecting iron ions.